Graphene and carbon nanotubes : ultrafast relaxation dynamics and optics - Malic, Ermin; Knorr, Andreas (Physicist); Winnerl, Stephan (Weinheim : Wiley, 2013)
The book introduces the reader into the ultrafast nanoworld of graphene and carbon nanotubes, including their microscopic tracks and unique optical finger prints. The author reviews the recent progress in this field by combining theoretical and experimental achievements. He offers a clear theoretical foundation by presenting transparently derived equations. Recent experimental breakthroughs are reviewed. This makes the book suitable for a wider audience, from graduate students and to researchers in academia and industry working on optoelectronic devices, renewable energies, and in the semicond.
4.2.3 Phonon-Induced Relaxation Channels4.3 Optically Induced Nonequilibrium Carrier Distribution; 4.4 Carrier Dynamics; 4.4.1 Orientational Relaxation toward an Isotropic Carrier Distribution; 4.4.2 Thermalization of the Excited Carrier System; 4.4.3 Energy Dissipation and Carrier Cooling; 4.4.4 Time- and Momentum-Resolved Relaxation Dynamics; 4.4.5 Differential Transmission Spectra; 4.5 Phonon Dynamics; 4.5.1 Momentum-Resolved Dynamics; 4.5.2 Time-Resolved Dynamics; 4.5.3 Momentum- and Time-Resolved Dynamics; 4.6 Pump Fluence Dependence; 4.6.1 Thermalization.
4.6.2 Isotropic Carrier Distribution.
Includes bibliographical references and index.
Print version record.
Keywords: Graphene; Nanostructures; Nanotubes; Electronic books